Synthesis of Iron Oxide/Polyaniline/Reduced Graphene Oxide Nanocomposite Materials as Active Sensing Material - Hussein, N.A.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Ternary hybrid materials have gained significant attention in recent years due to their unique synergistic effect shown to enhance the performance of devices in a variety of applications. In this present work, a novel ternary hybrid nanocomposite of -Fe2 O3 PANI-RGO was synthesized and hybrid together through ex-situ method to hybrid them into nanocomposite materials. The as-synthesized hybrid nanocomposite was subjected to physico-chemical characterization by x-ray diffraction and FTIR spectroscopy study. The experimental results observed that the hybrid materials have the individual material's peak suggesting that they are blending well, and it was confirmed with FTIR analysis where the functional group and vibrational mode was studied. The crystallite size calculated from Debye-scherrer equation shows that the materials are in nano size. The RGO material shows a good responsive towards 100ppm acetone where the response and recovery time was 7.01 and 7.71s respectively. Â© 2021 IEEE.